EFFORTS OF THE ELECTION COMMISSION OF INDIA TO PROTECT THE VOTING RIGHTS OF OVERSEAS INDIANS - A STUDY - Gogadia, Umesh Ashok; Patil, Yogeshwar Subhash (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Universal adult franchise, also known as general franchise, provides the right to vote to all adult citizens (18 years and above) irrespective of caste, religion, colour, education and economic status. The adult franchise system is the foundation of a democratic system. And it is based on the principle of equality. There has been a significant increase in voter registration in India in the last few years. However, the declining voter participation is a cause for concern. The 2019 general elections saw a voter turnout of 67.4%. Voter turnout in India is relatively high. Yet, on average, one in three voters did not vote in 2019. The Election Commission of India finds that over 300 million voters do not exercise their franchise and that there is a large disparity in the turnout in the assembly and Lok Sabha elections. Apart from urban apathy (people not coming to cities to vote), adult apathy, intra-state migration, is an important reason for participation in the electoral process. This is an important reason to pay attention to. Work, education, marriage, can lead to intra-state migration. According to the Election Commission, 85% of the total migration is within states. According to the 2011 census, 45.36 crore Indians in India, or (37%) people, are migrants. That is, they have now become permanent residents of a different place from their previous place of residence. However, 75% of such migration is due to marriage and family reasons. All these factors are seen to have an impact on the voting percentage of the Election Commission. The Election Commission is trying to find solutions to all these issues and increase the voter turnout percentage. Accordingly, the presented topic is suitable for research.